On the road to better routes: Five decades of published research on the vehicle routing problem. Issue 1 (24th April 2020) - Wang, Xingyin; Wasil, Edward
Abstract: For nearly 50 years, Networks has been at the forefront of routing research and practice with more than 140 articles in print with tens of thousands of citations. These articles span the development of solution procedures to reporting practical applications. We identify key areas of contribution including exact algorithms, heuristics, arc routing, and periodic routing, and provide detailed annotations for important articles in each area. Our survey reveals the rich heritage of published routing work that continues to influence the field today.